Hematological Changes in Salmonella Paratyphi A Infected Pullets - A. O. Ogunleye; A. T.P. Ajuwape; A. I. Adetosoye (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2009)
The hematology of 25 pullets experimentally infected orally with 0.5 mL of 1 x 107 cfu/mL of Salmonella Paratyphi A was studied. By day 4 post-infection (p.i.), dullness, ruffled or unkempt feathers, somnolence, yellowish-green diarrhea, and decreased water and feed consumption were observed. Hematological parameters of the birds were monitored on days 7, 14 and 21 p.i. The values were analyzed with Duncan’s Multiple range test, at P < 0.05. The packed cell volume (PCV) was significantly higher at day 7 p.i. than during pre-infection and at day 21 p.i. However, it was similar at days 7 and 14 p.i. Likewise, hemoglobin concentrations in the birds were similar during pre-infection, and at days 14 and 21 p.i. In contrast, they were significantly higher at day 7 than during pre-infection and at day 21 p.i. The indicators of anemia showed no significant differences between pre- and post-infection values. The period coincided with that of decreased feed and water consumption in the course of the disease. There were no significant differences in total leukocyte counts for days 7, 14 and 21 p.i., whereas they were significantly (P < 0.05) lower during pre-infection than at days 7, 14 and 21 p.i. The course of Salmonella Paratyphi A infection depends on the infective dose of the organism. There was no anemia in pullets; leukocytosis was attributable to heterophilic leukocytosis, lymphocytosis, monocytosis and eosinophilia, which are indicators of acute infection and internal stress, to which the pullets adequately responded.